CONTROL OF 36CL PRODUCTION IN CARBONACEOUS SHALES BY PHOSPHATE MINERALS - Chmiel G.; Fritz S.J.; Elmore D. (My University, 2003)
When using 36Cl to date very old groundwater in regional aquifer systems, knowledge of the subsurface 36Cl input into the aquifer system is essential. Although 36Cl can be produced through nuclear reactions in the subsurface, in many situations, the input of 36Cl into sedimentary aquifer systems by this avenue of production can be neglected. This is a valid assumption when investigating long-flowpath groundwater systems composed of sandstones, limestones, and shales of typical composition. These rock types are not sufficiently enriched in radioactive elements to produce significant 36Cl in the deep subsurface. Carbonaceous shales, on the other hand, can concentrate the radioactive elements necessary to produce significant 36Cl in the deep subsurface. Chlorine-36 ratios (36Cl/Cl) for a suite of Late Devonian and Pennsylvanian carbonaceous shales were calculated from bulk-rock chemistry as well as measured using accelerator mass spectrometry. The poor agreement between calculated and measured ratios is the result of the assumption of chemical homogeneity used by the calculation algorithm, an assumption that was not satisfied by the carbonaceous shales. In these shales, organic matter, clay minerals, and accessory minerals are heterogeneously distributed and are physically distinct on a micron-order scale. Although organic matter and clay minerals constitute the overwhelming bulk of the shales, it is the phosphate minerals that are most important in enhancing, and suppressing, 36Cl production. Minerals such as apatite and carbonate-apatite (francolite)-by including uranium, rare earth elements (REEs), and halogens-have an important impact on both neutron production and thermal neutron absorption. By incorporating both uranium and fluorine, phosphate minerals act as neutron production centers in the shale, increasing the probability of 36Cl production. By incorporating REEs and chlorine, phosphate minerals also act to shield 35Cl from the thermal neutron flux, effectively suppressing the production of 36Cl. To reconcile the measured 36Cl ratios with the ratios calculated assuming chemical homogeneity, the shales were artificially split into three fractions: organic, clay mineral, and phosphate mineral. Neutron production was calculated separately for each fraction, and the calculation results demonstrated that the phosphate fraction exerted much more control on the 36Cl ratio than the organic or clay mineral fractions. By varying the uranium and chlorine contents in the phosphate fraction, a new, heterogeneous 36Cl ratio was calculated that agreed with the measured ratio for the overwhelming majority of the carbonaceous shales. When using rock chemistry to calculate the 36Cl ratio, rock types that show mineralogical heterogeneity on a micron scale can be divided into bulk fractions and accessory fractions for separate calculations of neutron production and neutron absorption. In this manner, a more accurate, heterogeneous 36Cl ratio can be calculated for the rock as a whole.
Keywords: Devonian; Pennsylvanian; Paleozoic::Devonian; Палеозой::Каменноугольная; Палеозой::Девонская; Paleozoic::Carboniferous::Pennsylvanian